IMPLIKASI YURIDIS PUTUSAN MK NOMOR 46/PUU-VIII/2010 TERKAIT PERLINDUNGAN HAK ANAK - Mochammad Fahruz Rizqy (Yuridika, 2015)
By means of its decision number 46/PUU-VIII/2010, the Constitutional Court has made a breakthrough which intend to guarantee the fulfillment of civil rights for a child born out of wedlock from his/her both parents. By the fulfillment of civil rights, justice has been materialized for the child, as viewed from the perspective of the theory of justice.